Using semi-supervised learning to detect beluga whales from aerial image sequences - Mohammed G. Al-Jassani; Chiron Bang; Gregory O’Corry-Crowe; Cortney A. Watt; Mark Gillespie; Hanqi Zhuang (Frontiers in Marine Science, 2026)
Introduction Precise population monitoring of beluga whales ( Delphinapterus leucas ) is crucial for Arctic conservation management; yet, the manual annotation of aerial drone imagery is costly and logistically challenging. Calf detection is particularly important because calf presence and survival rates are indicators of reproductive health, recruitment success, and long-term population viability. However, calves are challenging detection targets due to their smaller size, lower frequency, and greater variability in appearance compared with adults. Although deep learning-based object detection offers considerable potential for automated wildlife monitoring, supervised approaches typically require large quantities of manually annotated data, limiting their application in conservation programs with restricted annotation resources. Methods This study systematically evaluated semi-supervised marine mammal detection from aerial imagery by comparing SEMI-DETR, a semi-supervised detection transformer, with four variants of YOLO11 across seven annotation budgets ranging from 1% to 50% of labeled data. Experiments were conducted using a bespoke dataset of 7,655 high-resolution aerial drone images annotated for adult and calf classifications. Results SEMI-DETR achieved a mean Average Precision (mAP) of 19.2 at 0.5:0.95 using only 34 labeled images (1% annotation budget), representing a 20% relative improvement over the best-performing supervised baseline. The performance advantage peaked at +6.6 mAP points at the 5% labeling level. Semi-supervised learning particularly improved calf detection, achieving a 24.3% relative improvement at 1% labeling compared with 16.8% for adults. Overall, comparable detection performance could be achieved with a 5- to 10-fold reduction in annotation requirements without substantially compromising detection quality. Discussion These findings demonstrate that semi-supervised learning can substantially reduce annotation requirements for automated marine mammal detection, with particularly strong benefits for the detection of calves. Improved calf detection has direct implications for population assessment and the monitoring of reproductive success and recruitment in beluga populations. This study establishes an empirical benchmark for semi-supervised marine mammal detection and provides practical guidance for allocating limited annotation resources in wildlife monitoring and conservation applications.

Hindsight informs foresight: revisiting millennial forecasts of impacts and status of rocky shores in 2025 - Stephen J. Hawkins; Kathryn A. O'Shaughnessy; George M. Branch; Laura Airoldi; Simon Bray; Paul Brooks; Michael T. Burrows; Juan Carlos Castilla; Tasman P. Crowe; Thomas W. Davies; Louise B. Firth; Keith Hiscock; et al. (Marine Pollution Bulletin, 2025)

Use of tusks by narwhals, Monodon monoceros, in foraging, exploratory, and play behavior - Greg O’Corry-Crowe; Maha Ghazal; Mark Gillespie; Paul Galvin; Jason Harasimo; Luke Storrie; Cortney A. Watt (Frontiers in Marine Science, 2025)
Despite the universal fascination with the tusk of the narwhal, the function of this long, spiraled tooth is still debated, primarily because few people have observed how narwhals ( Monodon monoceros ) use their tusks in the wild. Using an unmanned aerial vehicle (UAV), we recorded previously unreported interactions between multiple narwhals, Arctic char ( Salvelinus alpinus ) and glaucous gulls ( Larus hyperboreus ) in Canada’s High Arctic. Narwhals were recorded chasing char and using their tusks to hit, manipulate and influence the behavior of fish. Differences in tusk use likely reflected differences in behavioral intent with some actions associated with prey capture and others with exploration and likely play. Kleptoparasitic behavior by gulls when narwhals pursued char near the surface substantially reduced prey capture for narwhals. Associative and interactive behaviors among narwhals were linked to the ecological context including fish density and gull behavior. Some interactions appeared competitive in nature while others may have been communicative and affiliative. This study revealed that narwhals can use their tusks to investigate and manipulate objects, including prey, and deliver sufficient force with their tusks to stun and possibly kill fish. The speed and agility of char combined with kleptoparasitic behavior of gulls indicate that char may be a challenging species to predate while aspects of the narwhals’ actions may include social learning and exploration of a novel prey species, and are the first reported evidence of likely play, specifically exploratory-object play, in narwhals.

Perspectives in cattle reproduction for the next 20 years – A European context - Osvaldo Bogado Pascottini; Alan D. Crowe; Uxía Yáñez Ramil; Miel Hostens; Geert Opsomer; Mark A. Crowe (Theriogenology, 2025)

Effect of repeated low doses of gonadotropin-releasing hormone on the secretion of luteinizing hormone and follicle-stimulating hormone, and ovarian function in dairy cows suffering from anovulation type I - Wojciech Barański; Arkadiusz Nowicki; Mark A. Crowe; Dawid Tobolski; Sławomir Zduńczyk (Animal Reproduction Science, 2024)

A response-surface approach into the interactive effects of multiple stressors reveals new insights into complex responses - Paul R. Brooks; Mark Anthony Browne; Lisandro Benedetti-Cecchi; Devin A. Lyons; Tasman P. Crowe (Frontiers in Marine Science, 2023)
Understanding the difficult to predict interactive effects of anthropogenic stressors is recognized as one of the major challenges facing environmental scientists and ecosystem managers. Despite burgeoning research, predicting stressor interactions is still difficult, in part because the same two stressors can interact, or not, depending on their intensities. While laboratory experiments have provided useful insights about how organisms respond to serial doses of single stressors, we lack ‘response-surface’ field experiments in which naturally occurring assemblages are exposed to multiple types and concentrations of stressors. Here we used a field-based dosing system combined with a ‘response-surface’ design to test the individual and combined effects of two stressors (copper and chlorpyrifos) at five concentrations of each, for a total of 25 replicated treatments (n=4). After six weeks of dosing, chemical uptake and impacts at several levels of biological organization in mussel assemblages were measured. Stressor combinations produced interactive effects that would not have been revealed without using this replicated ‘response-surface approach’. Results show that non-additive effects of multiple stressors may be more complex and more common than previously thought. Additionally, our findings suggest that interactive effects of multiple stressors vary across levels of organization which has implications for monitoring and managing the chemical, biological and ecological impacts of priority pollutants in the real world.

Transfer of bovine embryos into a uterus primed with high progesterone concentrations positively impacts fetal development at 42 days of gestation - Maria Belen Rabaglino; José María Sánchez; Michael Mc Donald; Mark A. Crowe; Elena O'Callaghan; Pat Lonergan (Theriogenology, 2023)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Global transcriptomic profiles of circulating leucocytes in early lactation cows with clinical or subclinical mastitis - Zhangrui Cheng; Laura Buggiotti; Mazdak Salavati; Cinzia Marchitelli; Sergio Palma-Vera; Alistair Wylie; Haruko Takeda; Lijing Tang; Mark A. Crowe; D. Claire Wathes; Mark Crowe; Niamh McLoughlin; et al. (Molecular Biology Reports, 2021)

Examining the roles of working memory and visual attention in multiple object tracking expertise - David J. Harris; Mark R. Wilson; Emily M. Crowe; Samuel J. Vine (Cognitive Processing, 2020)
When tracking multiple moving targets among visually similar distractors, human observers are capable of distributing attention over several spatial locations. It is unclear, however, whether capacity limitations or perceptual–cognitive abilities are responsible for the development of expertise in multiple object tracking. Across two experiments, we examined the role of working memory and visual attention in tracking expertise. In Experiment 1, individuals who regularly engaged in object tracking sports (soccer and rugby) displayed improved tracking performance, relative to non-tracking sports (swimming, rowing, running) ( p = 0.02, η p 2 = 0.163), but no differences in gaze strategy ( ps > 0.31). In Experiment 2, participants trained on an adaptive object tracking task showed improved tracking performance ( p = 0.005, d = 0.817), but no changes in gaze strategy ( ps > 0.07). They did, however, show significant improvement in a working memory transfer task ( p < 0.001, d = 0.970). These findings indicate that the development of tracking expertise is more closely linked to processing capacity limits than perceptual–cognitive strategies.

Thermal stress responses in the bacterial biosphere of the G reat B arrier R eef sponge, R hopaloeides odorabile - Rachel Simister; Michael W. Taylor; Peter Tsai; Lu Fan; Timothy J Bruxner; Mark L Crowe; Nicole Webster (Environmental Microbiology, 2012)
Summary Marine sponges are diverse, abundant and provide a crucial coupling point between benthic and pelagic habitats due to their high filtration rates. They also harbour extensive microbial communities, with many microbial phylotypes found exclusively in sponge hosts and not in the seawater or surrounding environment, i.e. so‐called sponge‐specific clusters ( SCs ) or sponge‐ and coral‐specific clusters ( SCCs ). We employed DNA (16 S rRNA gene) and RNA (16 S rRNA )‐based amplicon pyrosequencing to investigate the effects of sublethal thermal stress on the bacterial biosphere of the G reat B arrier R eef sponge R hopaloeides odorabile . A total of 8381 operational taxonomic units ( OTUs ) (97% sequence similarity) were identified, affiliated with 32 bacterial phyla from seawater samples, 23 bacterial phyla from sponge DNA extracts and 18 bacterial phyla from sponge RNA extracts. Sublethal thermal stress (31° C ) had no effect on the present and/or active portions of the R. odorabile bacterial community but a shift in the bacterial assemblage was observed in necrotic sponges. Over two‐thirds of DNA and RNA sequences could be assigned to previously defined SCs / SCCs in healthy sponges whereas only 12% of reads from necrotic sponges could be assigned to SCs / SCCs . A rapid decline in host health over a 1° C temperature increment suggests that sponges such as R . odorabile may be highly vulnerable to the effects of global climate change.

Climate change causes rapid changes in the distribution and site abundance of birds in winter - ILYA M. D. MACLEAN; GRAHAM E. AUSTIN; MARK M. REHFISCH; JAN BLEW; OLIVIA CROWE; SIMON DELANY; KOEN DEVOS; BERNARD DECEUNINCK; KLAUS GÜNTHER; KARSTEN LAURSEN; MARC VAN ROOMEN; JOHANNES WAHL (Global Change Biology, 2008)
Detecting coherent signals of climate change is best achieved by conducting expansive, long‐term studies. Here, using counts of waders ( Charadrii ) collected from ca. 3500 sites over 30 years and covering a major portion of western Europe, we present the largest‐scale study to show that faunal abundance is influenced by climate in winter. We demonstrate that the ‘weighted centroids’ of populations of seven species of wader occurring in internationally important numbers have undergone substantial shifts of up to 115 km, generally in a northeasterly direction. To our knowledge, this shift is greater than that recorded in any other study, but closer to what would be expected as a result of the spatial distribution of ecological zones. We establish that year‐to‐year changes in site abundance have been positively correlated with concurrent changes in temperature, but that this relationship is most marked towards the colder extremities of the birds' range, suggesting that shifts have occurred as a result of range expansion and that responses to climate change are temperature dependent. Many attempts to model the future impacts of climate change on the distribution of organisms, assume uniform responses or shifts throughout a species' range or with temperature, but our results suggest that this may not be a valid approach. We propose that, with warming temperatures, hitherto unsuitable sites in northeastern Europe will host increasingly important wader numbers, but that this may not be matched by declines elsewhere within the study area. The need to establish that such changes are occurring is accentuated by the statutory importance of this taxon in the designation of protected areas.

Blood vessels in liver metastases from both sarcoma and carcinoma lack perivascular innervation and smooth muscle cells. - Shahzad Ashraf; Marilena Loizidou; Rahima Crowe; Mark Turmaine; Irving Taylor; Geoffrey Burnstock (Clinical & Experimental Metastasis, 1997)